Fever of Unknown Origin in Children: Optimization of Diagnostic Search (Part I) - B.A. Bezkaravayny; A.N. Voloshin; N.A. Yakovenko; S.V. Sumanov (Zaslavsky O.Yu., 2014)
The first part of the article contains general data about fever of unknown origin, its etiological structure. There is provided the most important clinical information about infectious and oncological diseases, which initially can not be diagnosed and designated as fever of unknown origin. The description of these diseases is represented in concise unified form.